Technology innovation for patients with kidney disease. (3rd October 2015) - Mitsides, Nicos; Keane, David F.; Lindley, Elizabeth; Mitra, Sandip
Abstract: The loss of kidney function is a life-changing event leading to life-long dependence on healthcare. Around 5000 people are diagnosed with kidney failure every year. Historically, technology in renal medicine has been employed for replacement therapies. Recently, a lot of emphasis has been placed on technologies that aid early identification and prevent progression of kidney disease, while at the same time empowering affected individuals to gain control over their chronic illness. There is a shift in diversity of technology development, driven by collaborative innovation initiatives such the National Institute's for Health Research Healthcare Technology Co-operative for Devices for Dignity. This has seen the emergence of the patient as a key figure in designing technologies that are fit for purpose, while business involvement has ensured uptake and sustainability of these developments. An embodiment of this approach is the first successful Small Business Research Initiative in the field of renal medicine in the UK.